TO THE PROBLEM OF THE FUNCTIONING OF BAILIFFS IN LUTS'K IN XV - FIRST HALF OF XVII CENTURIES: Autocomplete report made on February 8, 2016 at the meeting of Historical Urban seminar in Ukrainian Catholic University (City: History, Culture, Society, 2017)
Autocomplete report made on February 8, 2016 at the meeting of Historical Urban seminar in Ukrainian Catholic University
Keywords: Luts'k; bailiff; Early Modern times